Verification of Performance in Results-Based Financing : The Case of Panama's Health Protection for Vulnerable Populations (PSPV) Program - Perazzo, Alfredo (World Bank, Washington, DC, 2016)
Verification differentiates results-based financing (RBF) from other health-financing mechanisms, and it is considered an important process of RBF program design and implementation. Despite the vital role it plays in RBF, not much has been written about verification as a process, and information about different elements of the process, frequency, cost, and direct and indirect effects among others, is scarce. Panama’s Health Protection for Vulnerable Populations Program (PSPV) uses an RBF mechanism to deliver health services to the country’s rural poor. As in many RBF schemes, a major component of the PSPV is the verification of results. This study focuses on PSPV’s verification process, highlights its results and their application, and identifies lessons learned. Such information is useful to policy makers and technical experts interested in or designing RBF mechanisms.